Pertanggungjawaban Hukum dan Perlindungan Hukum Notaris Terhadap Kewenangannya Membuat Party Acte - Rama Andika, I Gusti Ngurah Md; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
This research has purpose to inform about law protection and responsibilities Notary for party acte they have made. This research is studied using normative methodthat based on the theory of responsibility and protection that help to emphasize the scope of both, so that the legal responsibilities and protections for Notaries can be identified in making a party act. The results of this study conclude that there are three (3) forms of legal responsibility of a Notary in making a party act, namely first legal responsibility for the UUJN and applicable laws and regulations, second legal responsibility based on sanctions, namely administrative, criminal and civil, third absolute legal responsibility and based on error. Legal protection for a Notary is provided by laws and regulations through the rights/obligations of a Notary and based on an institution, is given by the Notary Honorary Council. The position of a Notary who is noble and dignified must be carried out with full responsibility and protected by law from parties who want to degrade the position of a Notary.